2016
DOI: 10.1590/2446-4740.05615
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the mechanical competence parameter of the trabecular bone: a neural network approach

Abstract: Introduction: The mechanical competence parameter (MCP) of the trabecular bone is a parameter that merges the volume fraction, connectivity, tortuosity and Young modulus of elasticity, to provide a single measure of the trabecular bone structural quality. Methods: As the MCP is estimated for 3D images and the Young modulus simulations are quite consuming, in this paper, an alternative approach to estimate the MCP based on artificial neural network (ANN) is discussed considering as the training set a group of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This creates the opportunity to explore different methods of evaluation of the maximum stress in the pedicular screw positioning. Artificial neural network (ANN) is one method that has been used to determine the mechanical structure of bones [5]. It has also been shown that this model can be trained to reproduce results from finite element analysis of pedicle screws [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This creates the opportunity to explore different methods of evaluation of the maximum stress in the pedicular screw positioning. Artificial neural network (ANN) is one method that has been used to determine the mechanical structure of bones [5]. It has also been shown that this model can be trained to reproduce results from finite element analysis of pedicle screws [6].…”
Section: Introductionmentioning
confidence: 99%
“…An activation function is used to introduce nonlinearity to the model [17]. This model has been used to emboss the mechanical stress in the bone and biomechanical systems such as pedicle screw fixation [5,6,13,18].…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of ANNs is their ability to generalize or learn from examples 17 ; that is, ANNs can generalize learned information to provide satisfactory results for cases not seen in training. Therefore, ANNs have been used in many fields, such as chemistry 18 , geology 19 , medicine 20 , neurocomputations 21 and biomedical engineering 22 , among others.…”
Section: Introductionmentioning
confidence: 99%